A Professional Development Model for Math and Science Educators in Catholic Elementary Schools: Challenges and Successes - Kuchey, Debora; Morrison, Julie Q.; Geer, Cynthia H. (Catholic Education: A Journal of Inquiry and Practice, 2009)
Catholic elementary schools must continue to invest in the professional development of math and science teachers in order to prepare students for the challenging work that lies ahead of them. The purpose of the study was to examine the degree to which the Initiative for Catholic Schools (ICS), a 2-year professional development program for science and math teachers, demonstrated positive outcomes within the context of Catholic elementary education across the five levels of impact for a professional development program: participants’ reactions, participants’ learning, organization support and change, participants’ use of new knowledge and skills, and student learning outcomes. The results provide evidence of positive outcomes in the participants’ reactions, participants’ learning, organization support and change, and participants’ use of new knowledge and skills. The impact on student learning outcomes was less consistent and varied by grade level.